Technology priorities for the White House. - Kumagai, J.
What issues related to technology will the next US President confront? Vice President Al Gore and Texas Governor George W. Bush. Both offer up glowing words about the social, political, and economic wonders wrought by technology. Both promise, if elected, to keep that spirit of innovation alive. Regardless of who wins in November, the next Administration will confront a raft of technology-related problems. Some of these, like biotechnology and on-line privacy, have only begun to be taken up in policy circles. In more mature areas, like energy and air quality, and telecommunications, Federal rules may have unexpected downstream effects. And in issues that cross national borders, such as global warming, the so-called digital divide, and military policy, whatever path the new government takes will likely influence the course of events worldwide. Some of the main technological issues that will confront the new president are discussed including human genetics, the deepening digital divide, global warming, air pollution, electricity deregulation, privacy of information on computer networks, a national missile defence system, and telecommunication competition
Keywords: US President; Air pollution; Air quality; Biotechnology; Digital divide; Electricity deregulation; Energy; Global warming; Human genetics; Innovation; Military policy; National missile defence system; On-line privacy; Technology issues; Technology-related problems; Telecommunication competition